2021
DOI: 10.33545/surgery.2021.v5.i2f.716
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy: A comparative study

Abstract: The current study was done to compare the effectiveness, safety and clinical outcome between Laparoscopic and Open Appendectomy in terms of operating time, complications and length of hospital stay. Patients undergoing Appendectomy by Laparoscopic and Open technique from November 2016 to October 2017 were enrolled in the study after fulfilling eligibility criteria. According to surgical approach patients were randomly divided into two groups Laparoscopic Appendectomy Group (LA group) & Open Appendectomy Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our findings were supported by Singh et al 3 Our findings were supported by Resutra and Gupta 14 as they reported that 160 (80%) of the patients in Group A were completely satisfied with the scar and aesthetic result, 30 (15%) were moderately satisfied, and 10 (5%) were dissatisfied owing to the bad scar.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings were supported by Singh et al 3 Our findings were supported by Resutra and Gupta 14 as they reported that 160 (80%) of the patients in Group A were completely satisfied with the scar and aesthetic result, 30 (15%) were moderately satisfied, and 10 (5%) were dissatisfied owing to the bad scar.…”
Section: Discussionsupporting
confidence: 87%
“…A prior systematic review (SR) and meta-analysis (MA) on IAA found no difference between the two groups, implying that the laparoscopic method had certain advantages. 3 Since Semm's first study of laparoscopic appendectomy (LA) in 1983, a significant variety of research comparing laparoscopic vs. open appendectomy (OA) has been done. When compared to OA, LA has a distinct advantage in terms of peritoneal cavity access and visualisation via small incisions.…”
Section: Introductionmentioning
confidence: 99%
“…In 1981, German gynecologist Semm performed the first OA surgery, and then it is standardized among surgeons. It is usually done by a small lower right quadrant incision and is usually recovery after surgery is uneventful (8,9) .…”
Section: Introductionmentioning
confidence: 99%